Interactions between polydopamine and cellulose derivatives: Physicochemical aspects and applications - Furtado, Laise Moura (2023)
This thesis focused on the comprehension about the interactions between polydopamine (PDA) and cellulose esters or ethers. Such interactions enabled to explore the development of efficient adsorbents to treat synthetic and real wastes. The Chapter 1 comprises the physicochemical aspects regarding the effect of the surface energy of different substrates on the adhesion of PDA on them. The favorable interactions between PDA and cellulose acetate butyrate (CAB) led to the creation of PDA coated microbeads of CAB, which proved to be efficient adsorbents for caffeine from aqueous solutions. The results from the Chapter 1 inspired a study to better understand the interactions between CAB and caffeine, which is presented in the Chapter 2. The main findings reported the miscibility between the functional groups of CAB and caffeine and the sustained release of caffeine from CAB/caffeine films. The Chapter 3 shows the combination of sugarcane bagasse microparticles and hydroxypropyl methyl cellulose (HPMC) mediated by PDA to form adsorbents chemically and mechanically stable in aqueous medium. The high content of sugarcane bagasse microparticles (83 wt%) was challenging, but the adhesive properties of PDA helped keeping the particles together and HPMC provided plasticity to mold the adsorbents. The adsorbents were efficient towards the removal of dye (methylene blue), bisphenol A and to separate oil from water. The Chapter 4 presents the creation of adsorbents based on sugarcane bagasse microparticles (83wt%) and carboxymethyl cellulose (CMC) mediated by PDA. These adsorbents were successfully applied to treat the waste of undergraduate laboratory, which is a complex mixture of 17 metal ions at pH 1. The relevance of this study is the demonstration that the adsorbents were produced predominantly with agrowaste and efficiently treated a real waste from an undergraduate laboratory.